Very Severe Obstructive Sleep Apnea in Children: Outcomes of Adenotonsillectomy and Risk Factors for Persistence. (11th April 2017) - Isaiah, Amal; Hamdan, Hisham; Johnson, Romaine F.; Naqvi, Kamal; Mitchell, Ron B.
Abstract : Objectives: (1) To describe the clinical, demographic and polysomnographic (PSG) characteristics of children with very severe obstructive sleep apnea (OSA) without significant comorbidities; (2) to assess the outcomes following tonsillectomy and adenoidectomy (T&A); and (3) to determine predictors of persistence of OSA after T&A. Study Design: Case series with chart review. Setting: Tertiary‐level freestanding children's hospital. Subjects and Methods: Seventy‐four children aged 2 to 12 years who underwent T&A for very severe OSA (obstructive apnea‐hypopnea index [AHI] >30) were included. Children with significant comorbidities were excluded. PSG variables were compared pre‐ and post‐T&A using statistical tests. Factors affecting OSA resolution and persistence were studied. Results: The mean (95% confidence interval) age was 4.3 (3.8‐4.7) years with the majority black or Hispanic (64/74, 86%). The mean decrease in AHI after T&A was 49 (43‐58) ( P <. 001). Complete resolution of OSA, defined by an AHI <1, or an AHI <5 was seen in 32% (24/74) and 80% (59/74), respectively. Total sleep time (TST) greater than 5 minutes with end‐tidal CO2 >50 mm Hg was strongly associated with persistent OSA. The decrease in AHI post‐T&A was best predicted by higher preoperative oxygen saturation (SpO2 ) nadir and lower TST with SpO2 <90% ( R 2 = 0.24, P <. 001). Conclusions: T&A is associated with a significant improvement but not resolution of very severe OSA. The severity of baseline hypercapnia and hypoxemia may best predict persistent OSA after T&A. The study supports obtaining routine post‐T&A PSG in children with very severe OSA.